Factors Affecting Academic Burnout Among Nursing Students - Novianty, Lia; Said, Faridah Mohd; Nambiar, Nisha (Jurnal Keperawatan Komprehensif (Comprehensive Nursing Journal), 2025)
Aims: Students undergoing lectures will be faced with various demands and pressures in the academic field. Demands and pressures that cannot be overcome can cause students to be vulnerable to academic burnout which will have an impact on academic success. Academic self-efficacy, academic engagement, and social support are all factors that can help students avoid academic burnout. The purpose of this study was to see how academic self-efficacy, academic engagement, and social support affected academic burnout in nursing students. Methods: The nursing students at STIKes Sukabumi participated in a Cross Sectional Study for this research. 310 nursing students were selected at random using stratified sampling for this study. The data collection tools using questionnaires. The instruments used are the Maslach Burnout Inventory-Stundent Survey (MBI-SS), Academic Engagement Scale (AES), multidimensional scale of perceived social support (MSPSS) and College Academic Self-Efficacy Scale (CASES). Statistical analysis uses multiple linear regression Results: The results of this study show that academic self-efficacy affects academic burnout (b=-1,736, p=0,000), academic engagement affects academic burnout (b=-1,043, p=0,000), social support can affect academic burnout (b=-1,021, p=0,000) Conclusions: Academic self-efficacy, academic engagement, Social support, has an influence on academic burnout